Characteristics of Transition to Adulthood of Young People With Mental Health Problems - Ljubičić, Milana M.; Košutić, Željka G. (Sociološki pregled, 2019)
The paper will discuss the characteristics of transition in adulthood of young people with mental health problems. Foreign, and especially domestic scientific research on how these young people reach adulthood and whether they differ from their clinically invisible peers, is extremely rare. Therefore the aim of our analysis was to describe the characteristics of the way young people with the diagnosis of mental disorders grow up. In constructing the conceptual framework of the study we proceeded from the integrativesystemic model of transition. This is a model that respects the so-called, structural, as well as subjective markers of adulthood. The first group consists of objectively visible indicators of the place on the growing-up scale. The second group of indicators relates to the degree of the subjective independence of the young person from his/her parents. Our main research assumption is that along with gaining the structural indicators of growing up, the subjective independence of young people is increasing. The sample included 50 respondents - users of psychiatric services at the Daily Hospital of the Institute of Mental Health in Belgrade. The data were collected via a questionnaire and processed by statistical methods. Findings have shown that the respondents are highly dependent on their parents: in financial, residential, and emotional respects. The transition of these young people to the adulthood is difficult, and what is particularly concerning is that, compared to the younger people, the older respondents in the sample are more dependent on their parents in all analyzed indicators of the place on the growing-up scale. Further research should deal with the causes and consequences of the ongoing and/or discontinued growing-up process of young people diagnosed with mental disorders.Keywords: youth, mental disorder, adolescence, structural markers, subjective indicators